Etching of GeSe2 chalcogenide glass and its pulsed laser deposited thin films in SF6, SF6/Ar and SF6/O2 plasmas. (15th October 2020) - Meyer, T; LeDain, G; Girard, A; Rhallabi, A; Bouška, M; Němec, P; Nazabal, V; Cardinaud, C
Abstract: Excited species, reactive neutral species and positive ions, produced during the etching of Ge, Se and GeSe2 targets in inductively coupled plasmas, were identified by means of mass spectrometry (MS) and optical emission spectroscopy. The surface of etched Ge39 Se61 thin films were analyzed thanks to in situ x-ray photoelectron spectroscopy (XPS) and compared with those of Ge and Se etched samples. In 100% SF6, the successive adsorption of fluorine atoms forms SeF x ( x = 2, 4, 6) and GeF x ( x = 2, 4) stable and volatile products, generating a surface with few residues as interpreted with in situ XPS. The identification of SSe F x + ( x = 2, 3, 7) ions confirms that sulfur atoms play a role during the etching of Se-containing materials. A 0D kinetic model predicted the evolution of reactive neutral fluxes, ion fluxes and plasma parameters ( T e and n e ) in SF6 /Ar plasmas. It was found that the SeF6 and GeF4 concentrations, through Se F 5 + and Ge F 3 + MS signals, were related to the fluorine atom flux. In SF6 /O2, the simultaneous effect of fluorine and oxygen adsorption induces (Se) x –Ge– R 4− x environments ( R = F, O) at the surface of the Ge39 Se61 thin films.